2017
DOI: 10.1016/j.jad.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Affective traits and history of depression are related to ventral striatum connectivity

Abstract: Introduction Studying remitted Major Depressive Disorder (rMDD) facilitates a better understanding of neural mechanisms for risk, given that confounding effects of active symptoms are removed. Disrupted functional connectivity has been reported in multiple networks in MDD. However, no study to date of rMDD has specifically examined connectivity of the ventral striatum (VS), a region highly implicated in reward and motivation. We investigated functional connectivity of the VS in individuals with and without a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…Indeed, there are strong structural connectivity between insula and acknowledged reward-related regions ( Leong et al, 2016 ; Ghaziri et al, 2017 ). In line with our finding, previous neuroimaging study suggested that high risk for depression is related with the abnormal connection between OFC and insula during reward-related task ( DelDonno et al, 2017 ). Based on the crucial role of insula in representation of emotional awareness and interoceptive signals, this connectional abnormity was interpreted that the impaired integration of the value of loss with the emotional and interoceptive awareness is correlated with the occurrence of depression ( Rolls, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, there are strong structural connectivity between insula and acknowledged reward-related regions ( Leong et al, 2016 ; Ghaziri et al, 2017 ). In line with our finding, previous neuroimaging study suggested that high risk for depression is related with the abnormal connection between OFC and insula during reward-related task ( DelDonno et al, 2017 ). Based on the crucial role of insula in representation of emotional awareness and interoceptive signals, this connectional abnormity was interpreted that the impaired integration of the value of loss with the emotional and interoceptive awareness is correlated with the occurrence of depression ( Rolls, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has demonstrated network disruptions associated with CA (Pechtel and Pizzagalli, 2011 ; McEwen and Morrison, 2013 ; Philip et al ., 2013 ; Duncan et al ., 2015 ; Demir-Lira et al ., 2016 ). We have previously reported network disruptions related to depression in relation to ventral striatum, reward and personality traits (DelDonno et al ., 2017 ), hippocampus and memory (Rao et al ., 2016 ) and cognitive control and rumination (Stange et al ., 2017 ). The current study is the first to examine whether network alterations beyond those accounted for by rMDD diagnosis may be attributed to CA.…”
Section: Discussionmentioning
confidence: 99%
“…Striatal seeds consisting of bilateral 3.5 mm radius spheres were placed in the inferior ventral striatum, superior ventral striatum, dorsal caudate, dorsal rostral putamen, dorsal caudal putamen, and ventral rostral putamen. These predefined seeds were initially reported by Di Martino et al (2008) and have been repeatedly used in investigations of striatal connectivity (DelDonno et al, 2017; Fornito et al, 2013; Gabbay et al, 2013; Sarpal et al, 2016).…”
Section: Methodsmentioning
confidence: 99%